2017
DOI: 10.1177/1479972317741895
|View full text |Cite
|
Sign up to set email alerts
|

What kind of information and communication technologies do patients with COPD prefer to use? A cross-sectional study in Latin America

Abstract: The aim of the present study was to assess the frequency of uses and preferences of information and communication technologies (ICTs) among Latin American chronic obstructive pulmonary disease (COPD) patients. We conducted an anonymous cross-sectional survey study on Latin American COPD patients. The adapted version of the Michigan questionnaire was employed in eligible outpatients in different cities of Latin America. We categorized age and educational levels into three groups. The time passed since COPD diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Concerning respiratory diseases, SMS messages, WhatsApp, and Facebook have been mentioned as useful tools for receiving health information about chronic obstructive pulmonary disease (COPD) and also for communicating with a doctor [51]. However, in our study, respiratory diseases alone were not significantly associated with a preference for any specific eHealth resource.…”
Section: Summary Of Evidencecontrasting
confidence: 77%
“…Concerning respiratory diseases, SMS messages, WhatsApp, and Facebook have been mentioned as useful tools for receiving health information about chronic obstructive pulmonary disease (COPD) and also for communicating with a doctor [51]. However, in our study, respiratory diseases alone were not significantly associated with a preference for any specific eHealth resource.…”
Section: Summary Of Evidencecontrasting
confidence: 77%
“…WhatsApp is a cross-platform application that allows smartphone users to exchange not only text, but images, videos, and audio messages for free, and currently, the reported usage of this application in Latin America is considerably high. 26 On the other hand, Facebook is the largest social media platform in the world, allowing for complex social interactions with relatives and other people with similar interests. 27 Our results agree with recent estimates, suggesting that both WhatsApp and Facebook are amongst the most popular ICTs used by healthcare professionals for communicating and interacting with peers and patients.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have reported the use of social media as a valuable source of information and educational medium for patients with COPD [29, 30], to the best of our knowledge, this is the first SML study evaluating patients' perspectives on their disease. A cross-sectional study from Latin America by O jeda et al [30] suggested that understanding the preferences of information and communication channels among patients with COPD could help improve patient outcomes via addressing individual requirements. Recently, S inha et al [31] reported the impact of chronic cough on multiple aspects of patients' health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%